A partnership to reduce African American infant mortality in Genesee County, Michigan. - Pestronk, Robert M. (Association of Schools of Public Health, 2003)
A partnership in Genesee County, Michigan, has been working to reduce African American infant mortality. A plan was developed utilizing "bench" science and community residents' "trench" knowledge. Its theoretical foundation is ecological, grounded in a philosophy of public health as social justice, and based on the understanding that cultural beliefs and practices can be both protective and harmful. Partners agree that no single intervention will eliminate racial disparities and that interventions must precede, include, and follow the period of pregnancy. Core themes for the work include: reducing racism, enhancing the medical care and social services systems, and fostering community mobilization. Strategies include community dialogue and raising awareness, education and training, outreach and advocacy, and mentoring and support. The evaluation has several components: scrutinizing the effect of partnership activities on direct measures of infant health; analyzing changes in knowledge, attitudes, behaviors and other mediating variables thought to influence maternal and infant health; and effecting changes in personal and organizational policy and practice.